FORMATION OF A TOURIST CLUSTERS IN THE TERRITORY OF THE SHCHUCHINSK-BOROVOE RESORT ZONE (Journal of Geography and Environmental Management, 2022)
In world practice, the tourist cluster is considered as one of the most effective tools for increasing the competitiveness of the territory. The clustering of tourist space allows not only to streamline the interaction of all subjects interested in the development of tourism in the territory, but also to rationally develop the resources of the area within the framework of serving tourists. Today, enterprises of various profiles are involved in the process of serving tourists.Involving them in cluster structure will contribute to their active participation in a unified system of accumulating the value of the tourism product. However, process of clustering a tourist area is quite complicated and requires the study of both economic and geographical characteristics of the area.The purpose of this work is to consider the possibilities of forming a tourist cluster on the territory of the Shchuchinsk-Borovoe resort area. The significance of the study is due to the fact that the tourist potential of the study area has not been fully realized to date. It is required to develop measures that can significantly increase the attractiveness of the area for tourists.As part of considering possibilities of forming a cluster on the territory of the resort area, the authors used the methodology of cartographic taxonomy, which is based on the definition and description of taxa that can become significant elements of the cluster in the future. The analysis shows that the territory of the Shchuchinsko-Borovskoe resort area has all the necessary attributes to form a tourist cluster. The possible method of clustering the tourist area presented in the article, taking into account the specifics of the existing infrastructure, determines the value of the study, and the conclusions can be used in the development of measures to stimulate the development of tourism in the Akmola region.
Keywords: tourism cluster; tourism; geographic space; territory; destination; tourism services; integration